Needs Analysis of Augmented Reality Project-Based Learning Media for Enhancing Students' Critical Thinking Skills - Amirullah; Patahuddin patahuddin; Darman Manda (Celebes Journal of Elementary Education, 2026)
This study aims to conduct a needs analysis as a foundational step for developing Project-Based Learning (PjBL)-based Augmented Reality (AR) learning media to enhance students’ critical thinking skills. This research employed a research and development (R&D) approach using the ADDIE model, focusing on the analysis phase. The participants consisted of 40 elementary school students and 5 teachers. Data were collected through questionnaires, interviews, observations, and document analysis and were analyzed using descriptive statistics and thematic analysis. The findings indicate that students experience great difficulty in critical thinking while demonstrating very high interest in digital and interactive learning media. Teachers also reported a strong need for innovative instructional media and identified challenges in integrating technology into classroom practices. These results highlight a significant gap between current instructional approaches and the demands of digital-era learning. The novelty of this study lies in its emphasis on needs analysis as a basis for integrating PjBL and AR in instructional design. The study implies that the development of AR-based PjBL learning media has strong potential to enhance student engagement, support critical thinking, and create more meaningful learning experiences.